Cuidado maternal e cripticidade em Uloborus SP. (Araneae, Uloboridae) - Nascimento, Aline Leles (2015)
Predator-prey interactions play a key role in the evolution of adaptive mechanisms and aggressive postures in different animal groups. From this, organisms with colors and behaviors that reduce the risk of detection by natural enemies have a huge selective advantage over those who do not have this attribute. Species with maternal care can maximize their reproductive effort protecting eggs and offspring. In addition, aggressive behaviors against predators and other natural enemies appear to be essential to avoid the enemies attacks and increase offspring survivorship . Thus, in this study we aim to describe web building patterns during maternal behavior, and the influence of previous investment in reproduction and spider size on aggressive behavioral responses against artificial stimuli simulating attacks of predators. We also examined, from the perspective of view of natural enemies, if the colors of spiders and egg sacs are similar to each other and to the branches in which the webs are attached . We observed that females build modified webs during the period of egg sac protection, in which they are unable to capture prey and remain in a cryptic posture, aligned with their tubular egg sacs. Spiders carrying egg sacs showed aggressive responses to artificial stimuli and spiders without egg sacs always ran away or avoided the source of disturbance. Aggressive responses, however, were independent of clutch size and female body size. . Color analyzes showed that Hymenoptera and birds can not differentiate the colors of spiders and egg sacs, and of spiders and branches as well, showing the importance of color in decreasing detection from this specie.